Impulsivity in Alcohol Use Disorder: A Multidimensional Perspective - Müge Bozkurt; Cüneyt Evren (Addicta: The Turkish Journal on Addictions)
Impulsivity is a key construct in the development, maintenance, and escalation of drinking behavior, ulti- mately leading to alcohol use disorder. Because impulsivity is a multidimensional construct and has many ways of measurement, it is difficult to reach a clear consideration of its association with alcohol. Assessment of impulsive personality traits, impulsive choice, and impulsive action simultaneously in studies is recom- mended. On the other hand, impulsivity seems to be both a determinant and a consequence of alcohol use disorder. Short- and long-term effects of alcohol are also associated with increased impulsivity, further enhancing the risk for continued alcohol consumption and thus maintaining a cycle of use. Impulsivity is also considered an endophenotype, a heritable trait that can predict the likelihood of developing alcohol use disorder. Impulsivity can be a target for interventions, including cognitive-behavioral therapy and mindful- ness-based approaches, to improve impulse control and reduce relapse rates. A comprehensive understand- ing of its role in alcohol use disorder seems to be important for the development of effective treatment and prevention strategies.